THE USE OF IMPOLITENESS EXPRESSION IN "TITANIC" MOVIE BY JAMES CAMERON - Nurdani, Dian; Nur, Sahril; Mappaita, Suci Pole; Syamsuddin, Muh. Rifqi (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This research discusses the use of impolite expressions used in the Titanic movie using a qualitative approach. Impoliteness is a sentence of impoliteness which, if spoken, will have a negative impact, even to the point of harming yourself and others. Choosing good sentences in communication is very important because many people are very sensitive in listening to other people's words, so they have to take a lot of consideration before saying something and always pay attention to the conditions that are happening at that time. The main focus of this research is to analyze the types of impoliteness strategies used in the Titanic Movie. The method in this research uses a qualitative descriptive method. This research uses Culpeper's (1996) theory. Researchers found five types of impoliteness strategies used, namely: Bald on record impoliteness (7), Positive Impoliteness (11), Negative Impoliteness (14), Sarcasm or mock politeness (4), Withhold politeness (3). Based on this data, the researchers concluded that the strategy for using impoliteness in the Titanic movie that occurs most often is Negative impoliteness.